Profil Darah Merah dan Bobot Badan Ayam Broiler dipelihara pada Ketinggian Tempat yang Berbeda - Badru Zaman Habibi; Hanny Indrat Wahyuni; Endang Widiastuti (Journal Animal Research and Applied Science, 2019)
The aims of this research was determine the difference in the profile of red blood and body weight of broilers kept in the highlands and lowlands. The material of this study used 40 starter and finisher period chickens aged 21 and 35 days. The parameters observed were the profile of red blood and body weight. Data were analyzed using a t-test to test an average of 2 populations. The results showed that differences in place height were not significantly different (P> 0.05) in the number of erythrocytes and hemoglobin but were significantly different (p <0.05) in hematocrit and body weight. The conclusion of this study the profile of red blood broilers kept at different altitudes is still normal under the erythrocyte and hemoglobin level but the increase in temperature in the lowlands increases hematocrit values and decreases production seen from the body weight of broilers falling below normal.